2018
DOI: 10.14716/ijtech.v9i6.2360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrothermal Treatment on Grindability and Fuel Characteristics of Empty Fruit Bunch Derived Hydrochar

Abstract: Hydrothermal treatment (HTT) is recognized as one of the promising thermochemical pretreatments for biomass energy. It provides a low energy requirement and an elimination of predrying. Furthermore, a water washing method for the treated biomass is employed. One of the most promising biofuel candidates is empty fruit bunch (EFB) due to the large yearly production in Indonesia. In this study, the quality of hydrochars derived from EFB was assessed for its quality as a solid fuel. Raw EFB is thermochemically tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The potassium contents of the hydrochars (520.68908.86 mg/kg) were much lower in comparison to those of the parent biomass (4222.50 and 3206.66 mg/kg for corn cob and coconut shell respectively). This result aligns well with that obtained in a study by other researchers (Ruksathamcharoen et al, 2018). Since the potassium content corresponds to the tendency for combustion facilities to promote slagging and fouling, it is suggested that the resulting hydrochar shows potential as a feedstock for gasification.…”
Section: Resultssupporting
confidence: 91%
“…The potassium contents of the hydrochars (520.68908.86 mg/kg) were much lower in comparison to those of the parent biomass (4222.50 and 3206.66 mg/kg for corn cob and coconut shell respectively). This result aligns well with that obtained in a study by other researchers (Ruksathamcharoen et al, 2018). Since the potassium content corresponds to the tendency for combustion facilities to promote slagging and fouling, it is suggested that the resulting hydrochar shows potential as a feedstock for gasification.…”
Section: Resultssupporting
confidence: 91%
“…In the lab scale study, HTT of EFB was conducted at temperature of 180 • C, 200 • C and 220 • C for 30 min. Subsequent washed treatment was done for 15 min at 60 • C to further remove the alkali metal such K and Na [50]. In another study, HTT at 200 • C with 5 min holding time was capable of removing up to 90% of Ca, S, P, Mg, and K from corn stover, mischantus, switch grass and rice hull biomass [51].…”
Section: Hydrothermal Treatment Studies Of Oil Palm Solid Wastes and Mswmentioning
confidence: 99%
“…The hydrochar also offered low ash and sulphur content in comparison to Indonesian coal. Moreover, it was also found that the grindability of hydrochar was significantly better than the raw EFB which improved the fuel properties [50]. The development of HTT that enables utilization multi range of biomass to produce high quality pellet will significantly increase performance of Malaysian biomass pellet industry as commercialising second generation biofuel is stipulated in NKEA of oil palm industry under seventh EPPs of oil palm NKEA of the ETP of the oil, gas and energy sector in Malaysia.…”
Section: Hydrothermal Treatment Studies Of Oil Palm Solid Wastes and Mswmentioning
confidence: 99%
“…Here, pelletization is assumed as the compression method, and the bulk density of rice husk pellets was 0.6 t/m 3 , while the improvement rate of the bulk density by compression was 5 times. The rate of improvement of energy density through hydrothermal treatment could not be obtained from this experimental data, so it was set to 1.3-fold according to data in the literature for the hydrothermal treatment of cellulose [22] and Empty Fruit Bunches (EFB) [23]. Figure 17 shows the results for the computation of transportation costs that were calculated using the resource island model.…”
Section: The Resource Island Modelmentioning
confidence: 99%